Macromolecular and thermokinetic properties of a galactomannan from Sophora alopecuroides L. seeds: A study of molecular aggregation. (15th June 2021) - Guo, Rui; Li, Xujiao; Ma, Xianda; Sun, Xianbao; Kou, Yuxing; Zhang, Jun'ai; Li, Deshun; Liu, Yanfang; Zhang, Hui; Wu, Yan
Graphical abstract: Abstract: The molecular aggregation of a galactomannan (NSAP-25) from Sophora alopecuroides L. seeds was investigated, where three polydisperse systems were confirmed during particle size analysis, indicating existence of different aggregates composed of random coil chains revealed by circular dichroism. Morphologically, NSAP-25 aggregate of various sizes (200–1200 nm) was possibly multi-stranded and formed by ellipsoid-like particles (20–60 nm) composed of compact coil chain, exhibiting extended amorphous structure with chain-like branches intertwined. Hence, NSAP-25 aggregation was inevitable, which exerted an unignorable effect on augmenting flexibility ( β ↓, γ ↓, α ↓ and L p / M L ↓) and compactness ( ρ ↓, d f ↑ and C ∞ ↓) of branched random coil chain based on macromolecular analysis, especially when concentration increased. Moreover, it could be relevant to thermokinetic behavior of random nucleation and subsequent growth (A 2 model and negative Δ S *) as well as good thermal stability (IPDT, ITS, t 0.05, T m and T p ), thus conferring potential applications for NSAP-25 in food and pharmaceutical industries.